Effect of fertilization combination on cucumber quality and soil microbial community - Wang, Mei; Xu, Yu; Ni, Haiping; Ren, Shiai; Li, Ni; Wu, Yuxia; Yang, Yan; Liu, Yumin; Liu, Zongzheng; Liu, Yingchun; Shi, Jing; Zhang, Youming; et al. (Frontiers in Microbiology, 2023)
Due to the lack of scientific guidance on the usage of fertilizer, the overuse of chemical and organic fertilizer is commonly witnessed all over the world, which causes soil degradation and leads to environmental pollution. The effect of fertilizer strategies on soil properties, cucumber nutrients, and microbial community was investigated in this study with the aim to explore an optimized and enhanced fertilizer strategy. There were 5 fertilizer strategies conducted including CK (no fertilizer), M (cow dung manure only), NPK (chemical fertilizer only), NPKM (chemical fertilizer combined with manure), and DNPKM (30%-reducing chemical fertilizer combined with manure). It was found that different fertilizer strategies significantly affected the soil organic matter and nutrient levels and cucumber production and nutrient contents of the experimental field. Different fertilizer strategies showed dramatic effects on the alpha- and beta-diversity of soil microbial communities. Moreover, NPKM and DNPKM groups could significantly improve the bacterial abundance and fungal diversity. In addition, the structure of microbial communities was significantly changed in the presence of manure, chemical fertilizer, and their combination. Optimized combination of NPK with M improved the abundance of aerobic, biofilm formation-related, and Gram-negative bacteria and suppressed the anaerobic and Gram-positive bacteria. The presence of saprotrophs fungi was enhanced by all fertilizer strategies, especially the plethora of Gymnoascus. The combination of manure with chemical fertilizer could improve the availability of nutrients, and therefore reduce the adverse effects and potential risks induced by excessive fertilizer application. In conclusion, the new fertilization approach can not only meet the growth requirements of cucumber after reduced fertilization, but also protect soil health, which provides a new candidate for the eco-friendly technology to satisfy the topic of carbon neutrality.